Kemampuan Menulis Teks Berita Siswa Kelas VIII SMP Negeri 47 Pekanbaru - Fitranelda, Windya; Septyanti, Elvrin; Permatasari, Silvia (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to describe the level of ability to write news texts for class VIII students at SMP Negeri 47 Pekanbaru. This type of research is quantitative research that uses data derived from written skills tests. Then, the data that has been obtained is expressed in the form of numbers. The methods used to collect data in this research were observation techniques and writing skills tests by assigning students to write news texts. The population in this study was the entire class VIII students of SMP Negeri 47 Pekanbaru, totaling 148 people who were divided into 4 classes. The sample in this study consisted of 40 students. The results of this research show that the ability to write news texts for class VIII at SMP Negeri 47 was obtained on average in the medium category. In the title suitability aspect, the average score of the sample students is in the high category with a score of 86. In the news headline aspect, the average score of the sample students is in the high category with a score of 83. In the news body aspect, the average score of the sample students is in the medium category with a score of 80 and in the news tail aspect, the average score of the sample students is in the medium category with a score of 61.